Common Heritage of Mankind in Antarctica: Impossibility of Application in the territory because of lack of its essential characteristics and principles - Sutherland Condorelli, Giovannina (Universidad de Chile. Facultad de Derecho, 2019)
The Common Heritage of Mankind concept is analyzed and it is reviewed if its essential elements are or not present in the Antarctic case. The paper tries to find if it is or not possible to give this category to the Sixth Continent. Se analiza el concepto de Patrimonio Común de la Humanidad y se revisa si los elementos esenciales del mismo se cumplen o no en la Antártica. Se pretende concluir si es o no posible dar tal categoría al Sexto Continente.